Ei ordliste trekt ut av tre ordbøker/ordlister - Hovdenak, Marit (Nordiske Studier i Leksikografi, 1995)
The article deals with the compilation af a spelling dictionary, Nynorskordlista, based on three electronically stored sources. Two of the sources are printed dictionaries. The types of data extracted from each source are described. The data were combined in to the compilation format of Nynorskordlista. Some advantages of the method are discussed.